FAKTOR EKONOMI MAKRO TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PADA TAHUN 2009-2023 - Purwoko Adhi Pramono; Siti Aisyah (POLITEKNIK LP3I JAKARTA, 2025)
Economic expansion functions as a critical metric that signifies the financial vitality of a nation. In addition to the impediments presented by residual budget financing (SilPA), technological innovation, corruption, taxation, and educated unemployment, numerous other barriers obstruct Indonesia's economic advancement. This research endeavors to explore the diverse elements that impact economic growth. The analysis employed secondary data spanning from 2009 to 2023, obtained from the Central Statistical Agency (BPS), the Central Government Financial Report (LKPP), and the Corruption Eradication Commission (KPK). The approach utilized is the Ordinary Least Squares regression methodology (OLS). The results indicated that, while the variables of corruption and educated unemployment did not exhibit significant effects on economic growth, the factors of SilPA, technological innovation, and taxation demonstrated substantial impacts. It is anticipated that the government will proficiently manage SilPA to enhance infrastructure development and public services, along with optimizing the taxation framework.